Meningkatkan Keterampilan Berbicara Menggunakan Metode Teams Games Tournaments (TGT) - Muhammad Ridwan H Umar; Ahmad Ahmad (IAIN Manado, 2021)
Improving Speaking Skills Using the Teams Games Tournaments (TGT) Method. This classroom action research aimed at describing the speaking skill learning process using the Teams Games Tournaments (TGT) method for the first-year students of Indonesia Language and Literature Education, Muhammadiyah University of Kupang 2019/2020 academic year. The research was conducted in two cycles. The data were collected through observation, tests, and documentation. The data were analyzed quantitatively and qualitatively. The study showed that there was an improvement in the learning process and the student’s score after applying the Teams Games Tournaments method. Students were motivated and enthusiastic in learning activities. There was an active interaction between students and lecturers during the learning process. In addition, there was also an improvement in the students’ speaking skill scores. In the first cycle, the whole average of students’ score was 66.13 became 75,33 in the second cycle